2007
DOI: 10.1186/1472-6807-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of PA-IIL lectin from Pseudomonas aeruginosa – Unravelling the role of the specificity loop for sugar preference

Abstract: Background: Lectins are proteins of non-immune origin capable of binding saccharide structures with high specificity and affinity. Considering the high encoding capacity of oligosaccharides, this makes lectins important for adhesion and recognition. The present study is devoted to the PA-IIL lectin from Pseudomonas aeruginosa, an opportunistic human pathogen capable of causing lethal complications in cystic fibrosis patients. The lectin may play an important role in the process of virulence, recognizing specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…A comparison showed that in PA-IIL, Ser22 makes a hydrogen bond to the side chain of Asp96, preventing it from binding to O6 of mannose. We have recently demonstrated that by mutating the specificity loop residues the sugar specificity can be engineered, with the Ser22Ala PA-IIL mutant binding more strongly to mannose than to fucose [30].…”
Section: Structural Basis For Mannose Specificity and Possible Biologmentioning
confidence: 99%
“…A comparison showed that in PA-IIL, Ser22 makes a hydrogen bond to the side chain of Asp96, preventing it from binding to O6 of mannose. We have recently demonstrated that by mutating the specificity loop residues the sugar specificity can be engineered, with the Ser22Ala PA-IIL mutant binding more strongly to mannose than to fucose [30].…”
Section: Structural Basis For Mannose Specificity and Possible Biologmentioning
confidence: 99%
“…LecB (PA-IIL) is highly homologous to RSL and has similar affinity for fucose. [29] Thus, this experiment suggests that even simple glycomimetic structures can attain a significant amount of selectivity among lectins with analogous specificity. Work is in progress in our group to exploit array analysis of a larger group of glycomimetic structures towards the identification of lectin-selective glycomimetic entities.…”
Section: Discussionmentioning
confidence: 95%
“…To aid in adherence PA-IL and PA-IIL are positioned in the outer membrane of biofilm bacteria [ 23 ]. PA-IL binds preferentially to galactose whereas PA-IIL has a high affinity for monosaccharides especially fucose, thus contributing to biofilm formation [ 24 ]. In Pseudomonas aeruginosa these lectins are soluble, with evidence to suggest they are involved in both strengthening of established biofilms and adhesion to the airways of cystic fibrosis patients [ 25 ].…”
Section: Adhesion In the Gram-negative Bacteria Pseudomomentioning
confidence: 99%